Severity of prepregnancy diabetes on the fetal malformations and viability associated with early embryos in rats - Bueno, Aline [UNESP]; Sinzato, Yuri Karen [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Gallego, Franciane Quintanilha [UNESP]; Perecin, Felipe [UNESP]; Rodrigues, Tiago [UNESP]; Damasceno, Débora Cristina [UNESP] (Oxford University Press (OUP), 2020)
Preexisting/pregestational diabetes enhances the risk of birth defects. Several factors have been involved during the implantation process, such as cytokines (granulocyte-macrophage-colony-stimulating factor [GM-CSF]). The objective was to evaluate the effects of two levels of diabetes on the redox status of preimplantation embryos during the implantation process to comprehend how both are involved in embryo and fetal viability against maternal diabetes. Female Sprague-Dawley rats received streptozotocin at birth (mild diabetes [MD]) or at adulthood (severe diabetes [SD]) to obtain two experimental diabetes intensities. After confirming the diabetic status, the nondiabetic and diabetic groups were mated around day 110 of life. At gestational day (GD) 21, fetuses were assessed for viability and malformations and ovaries for embryo loss before implantation. Other pregnant nondiabetic and diabetic rats were sacrificed at GD2-4 for maternal and preimplantation embryo oxidative stress markers, maternal serum insulin, uterine fluid GM-CSF, and preimplantation embryo morphological analysis. MD and SD caused abnormal redox levels, lower GM-CSF and insulin levels during the preimplantation period, and embryonic loss before implantation. SD caused lower fetal viability and higher fetal malformation percentages at GD21. The SD dam-derived preimplantation embryos presented lower glutathione levels and higher thiobarbituric acid reactive substances concentration at GD3 and an increased frequency of abnormal preimplantation embryos at GD4. In conclusion, preexisting diabetes leads to complications in the implantation process. Furthermore, maternal oxidative stress and other metabolic changes alter the redox state and morphological structure of preimplantation embryos, contributing to damaged growth and development in late pregnancy.
Keywords: fetus; hyperglycemia; oxidative stress; pregestational; rat